Prevalence and associated factors of burnout among family medicine residents in Al Madina, Saudi Arabia - Sami A. R. Aldubai; Abdullah M Aljohani; Abdulwahab G Alghamdi; Khalid S Alghamdi; Kuru Ganasegeran; Ayman M Yenbaawi (Journal of Family Medicine and Primary Care, 2019)
Background and Aim: Burnout is a common problem for interns and residents. It has been associated with physical and mental health of health care providers as well as low job satisfaction and medical errors. Few studies have investigated this problem among residents. This study aimed to determine the prevalence of burnout and its associated factors among family residents in Al Madina city, Saudi Arabia. Materials and Methods: This cross-sectional study was conducted among 75 residents in the family medicine residency programs in Al Madina, Saudi Arabia. A self-administered questionnaire was used that includes questions on sociodemographic characteristics and sources of stress and burnout. T test, analysis of variance (ANOVA) test, and multiple linear regression analysis were employed. Results: Majority were female (54.7%) and aged 26 to 30 years (84.0%). The significant predictors of burnout in the final model were “tests/examinations” (P = 0.014), “large amount of content to be learnt” (P = 0.016), “unfair assessment from superiors” (P = 0.001), “work demands affect personal/home life” (P = 0.001), and “lack of support from superiors” (P = 0.006). Conclusion: Burnout is present among family medicine residents at a relatively high percentage. This situation is strongly triggered by work-related stressors, organizational attributes, and system-related attributes, but not socio-demographics of the respondents. Systemic changes to relieve the workload of family medicine residents are recommended to promote effective management of burnout.